2016
DOI: 10.1124/jpet.116.232009
|View full text |Cite
|
Sign up to set email alerts
|

Tiotropium Attenuates Virus-Induced Pulmonary Inflammation in Cigarette Smoke-Exposed Mice

Abstract: Viral infections trigger exacerbations in chronic obstructive pulmonary disease (COPD), and tiotropium, a M3 receptor antagonist, reduces exacerbations in patients by unknown mechanisms. In this report, we investigated whether tiotropium has anti-inflammatory effects in mice exposed to cigarette smoke (CS) and infected with influenza virus A/PR/8/34 (H1N1) or respiratory syncytial virus (RSV) and compared these effects with those of steroid fluticasone and PDE4-inhibitor roflumilast. Mice were exposed to CS; i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 58 publications
1
26
1
1
Order By: Relevance
“…It means that tiotropium may directly bind to some components of the replication complex and this most likely leads to the inhibition of SARS-CoV-2. Interestingly, tiotropium showed some antiviral effects on rhinovirus-infected human airway epithelial cells [ 40 ], RSV-infected human epithelial type 2 (HEp-2) cells [ 41 ] and lung tissues from cigarette smoke-exposed and RSV-infected mice [ 42 ]. Second, tiotropium has been shown to inhibit the TNF- and/or NFκB-signaling pathways, which were the most significantly upregulated pathways upon the infection of SARS-CoV-2 in NHBE cells.…”
Section: Resultsmentioning
confidence: 99%
“…It means that tiotropium may directly bind to some components of the replication complex and this most likely leads to the inhibition of SARS-CoV-2. Interestingly, tiotropium showed some antiviral effects on rhinovirus-infected human airway epithelial cells [ 40 ], RSV-infected human epithelial type 2 (HEp-2) cells [ 41 ] and lung tissues from cigarette smoke-exposed and RSV-infected mice [ 42 ]. Second, tiotropium has been shown to inhibit the TNF- and/or NFκB-signaling pathways, which were the most significantly upregulated pathways upon the infection of SARS-CoV-2 in NHBE cells.…”
Section: Resultsmentioning
confidence: 99%
“…The PDE4 inhibitor roflumilast N‐oxide partly reverses CS‐induced epithelial dysfunction (Milara et al ., 2014, 2012; Schmid et al ., 2015; Tyrrell et al ., 2015), and the PDE4 inhibitors, GPD‐1116 and piclamilast can prevent the development of CS‐induced emphysema and pulmonary hypertension in mice (Mori et al ., 2008; Seimetz et al ., 2015, p. 4). Zl‐n‐91, a selective PDE4 inhibitor can also suppress CS‐induced lung inflammatory in rats (Wang et al ., 2010; Bucher et al ., 2016). The aim of the present study was to investigate whether CS may directly induce changes in PDE expression or activity, thus contributing to lung pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the blockage of M3 receptor which gives rise to the bronchodilation, more attention has been paid to the anti-inflammatory effects of muscarinic antagonists [ 4 6 ]. In several animal models tiotropium has been found to attenuate acute and chronic pulmonary inflammation [ 30 32 ]. Several studies in vitro also showed that tiotropium could suppress LPS-induced the release of neutrophil chemotactic mediators by human airway epithelial cells, lung fibroblasts and alveolar macrophages [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%